Enhanced Bone Formation in Osteoporotic Mice by a Novel Transplant Combined with Adipose-derived Stem Cells and Platelet-rich Fibrin Releasates. (8th July 2020) - Sheu, Shi-Yuan; Hsu, Yuan-Kai; Chuang, Ming-Hsi; Chu, Chi-Ming; Lin, Po-Cheng; Liao, Jeng-Hao; Lin, Shinn-Zong; Kuo, Tzong-Fu
Osteoporotic fracture is the main complication of osteoporosis (OP) and accounts for millions of injuries annually. Local intervention by intra-marrow injection has been a good option for preventing osteoporotic bone loss when the osteoporotic femoral fracture has been treated. In this study, tail vein transplantations were examined to evaluate the cell-based therapeutic approach for treating OP with adipose-derived stem cells (ADSCs) and platelet-rich fibrin releasates (PRFr) in an ovariectomized (OVX) mice model. Thirty-six 12-wk-old female ICR mice were randomly divided into six groups: untreated control; sham-operated; OVX-control; OVX-ADSCs; OVX-PRFr; and OVX-ADSCs+PRFr. Starting 8 wk after ovariectomy, the OVX mice received tail vein injections once each week for four consecutive weeks, then were evaluated radiographically and histopathologically 8 wk after the first injection. We also assessed changes to bone trabeculae in the proximal tibial growth plate. In OVX mice treated with ADSCs or PRFr alone, or with a combination of ADSCs and PRFr, the trabecular bone mineral density (BMD), bone volume ratios (BV/TV), and numbers (Tb.N) in the proximal tibia areas were significantly higher than that in the OVX-control group. Significant differences between OVX-treated mice and OVX controls were found for trabecular separation, but not for trabecular thickness. These results indicate that ADSCs or PRFr treatment enhances bone microarchitecture in OP. The treatment of bone loss of OVX mice with ADSCs+PRFr induced greater bone consolidation with bone tissue production ( P < 0.01) when compared to the others. Thus, we conclude that the transplantation of ADSCs combined with PRFr might provide an alternative strategy for the treatment of various bone disorders in OP with an unlimited source of cells and releasates.